Terrestrial isopods (Crustacea: Isopoda: Oniscidea) from Brazilian caves. (October 2014) - Campos‐Filho, Ivanklin Soares; Araujo, Paula Beatriz; Bichuette, Maria Elina; Trajano, Eleonora; Taiti, Stefano
<x xml:space="preserve">Abstract</x> To date, six species of terrestrial isopods were known from Brazilian caves, but only four could be classified as troglobites. This article deals with material of Oniscidea collected in many Brazilian karst caves in the states of Pará, Bahia, Minas Gerais, Mato Grosso do Sul, and São Paulo, and deposited in the collections of the Museu de Zoologia, Universidade de São Paulo, the Coleção de Carcinologia do Departamento de Zoologia, Universidade Federal do Rio Grande do Sul, and the collection of the Natural History Museum, Section of Zoology 'La Specola', Florence. Three new genera have been recognized: Spelunconiscus gen. nov. and Xangoniscus gen. nov. (Styloniscidae), and Leonardoscia gen. nov. (Philosciidae). Twenty‐two species have been identified, 11 of which in the families Styloniscidae, Philosciidae, Scleropactidae, Plathyartridae, Dubioniscidae, and Armadillidae are new to science: Leonardoscia hassalli sp. nov., Metaprosekia quadriocellata sp. nov., Metaprosekia caupe sp. nov., Amazoniscus leistikowi sp. nov., Novamundoniscus altamiraensis sp. nov., Trichorhina yiara sp. nov., Trichorhina curupira sp. nov., and Ctenorillo ferrarai sp. nov. from Pará; Xangoniscus aganju sp. nov. from Bahia; and Spelunconiscus castroi sp. nov. and Trichorhina anhanguera sp. nov. from Minas Gerais. Four new species in the families Styloniscidae (Spelunconiscus castroi sp. nov. and Xangoniscus aganju sp. nov.), Philosciidae (Leonardoscia hassalli sp. nov.), and Scleropactidae (Amazoniscus leistikowi sp. nov.) with highly troglomorphic traits can be considered as troglobitic, whereas all the remaining species are either troglophilic or accidentals. Brazilian caves are now under potential threat because of recent legislation, and the knowledge of the subterranean biodiversity of the country is thus of primary importance. © 2014 The Linnean Society of London